Communicating Subjective Evaluations - Matthias Lang (Max Planck Institute for Research on Collective Goods, 2013)
Should principals explain and justify their evaluations? In this paper the principal's evaluation is private information, but she can provide some justifications by sending a costly message. Indeed, it is optimal for the principal to explain her evaluation to the agent if and only if the evaluation turns out to be bad. The justification guarantees the agent that the principal has not distorted the evaluation downwards. On the equilibrium path, as long as the principal provides a justification, the wage increases in the performance of the agent. For good performances, however, the principal pays a given high wage without providing justifications. This wage pattern fits empirical observations that subjective evaluations are lenient and discriminate poorly between good performances. I show that this pattern is part of the optimal contract instead of biased behavior. Furthermore, it is possible to implement the optimal contract in an ex-post budget-balanced way if stochastic contracts are feasible.
Keywords: D82; D86; M52; J41; 330; Communication; Justification; Subjective evaluation; Stochastic contracts; Disclosure; Vertragstheorie; Prinzipal-Agent-Theorie; Informationsverhalten; Kommunikation; Bewertung; Spieltheorie; Theorie